Exploring Children’s Connections to Nature Through Photovoice in School Environments - Walimbe, Sonali; Nandineni, RamaDevi; Rege, Sumita (MAJ - Malaysia Architectural Journal, 2025)
Schools play a pivotal role in shaping the formative experiences of children, influencing their academic and social development. It is crucial to understand the subjective perceptions of students regarding school spaces allocated or designed for them to know the significance of these spaces and how they are utilized. The primary aim of this study is to explore elements within the school-built environment that foster children’s connection to nature using the innovative photovoice method. Guided by the question, "How does the photovoice method enhance our understanding of children’s connection to nature, fostering both ecological sensitivity and equitable experiences within the school setting?" The students were briefed to shoot pictures of their 10 favourite places in the school premises and then participate in individual interviews. The results showcased a number of nuanced ways in which children connected with nature, emphasizing the ecological richness of the school environment. This research listens to children’s voices through the visual narrative of photovoice. It aims to inform future educational practices and environmental design strategies, emphasizing the dual goals of equity and ecological sustainability within school environments. This study enriches the current literature by employing photovoice as a method to explore school connectedness and identify elements fostering connection in the school environment. Notably, participants emphasized that experiences in the natural environment, facilitated through outdoor activities and observation, significantly contribute to an enhanced sense of school connection. To conclude, understanding and fostering nature connectedness in children within the school environment is a crucial aspect of providing quality education. The study’s emphasis on ecological sensitivity and aligns with the broader goals of environmental sustainability, contributing to both SDG 4 and SDG 15.